A Pilot Study on Developed Shoes That Enhance Gait Parameters Without Increasing Muscle Activity - Teppei Abiko; Shin Murata; Yoshihiro Kai; Hideki Nakano; Masashi Sakamoto; Keita Suzuki; Dai Matsuo; Michio Kawaguchi (Applied Bionics and Biomechanics)
This pilot study investigated the potential of a newly developed shoe design to improve gait parameters without altering muscle activity in healthy women. The shoe design features a V-shaped heel and a high-elasticity midsole, which are intended to enhance stability during heel contact and promote efficient load transfer throughout the gait cycle. Ten study participants underwent a randomized crossover design, wearing developed and general shoes during the trials. Spatiotemporal gait data and muscle activity were measured to assess the impact of the shoe design developed on gait efficiency. Significant improvements in gait speed, step and stride length, and swing time were observed with the developed shoes, indicating improved gait efficiency. Importantly, these improvements were achieved without significant changes in muscle activity, suggesting that the developed shoe design improves gait efficiency without increasing muscle workload. Considering the limitations of the small sample size and the exploratory nature of this pilot study, further research with a larger cohort is necessary to validate these preliminary findings.